Influência do tipo de fermento e do envelhecimento sobre a qualidade da cachaça artesanal orgânica - Gabriel, Afra Vital Matos Dias (2010)
The current market of artisanal cachaça has growing continuously in the last years, especially in the last decade. This is a result of governmental programs to stimulate low-scale producers, which correspond to 30% of the cachaça production in Brazil. These familiar producers have been using traditional and rudimentary processes and techniques, with a little or no quality control. The ferment is prepared in an artisanal way (caipira ferment or natural ferment), with autochthonous yeasts and bacteria present in the sugar cane juice. This obviously difficultates the quality control of the beverage, however, it may contribute to a better sensorial quality. The organic cachaça production appears to be a promising alternative for low-scale producers because the demand for natural products, healthy and ecologically correct is increasing. In this context, this work aimed to evaluate the contribution of the type of the ferment (caipira and commercial) and the ageing (in oak barrels) to the chemosensory quality of the cachaça and to the development of this agro-industrial segment. The fermentation with the caipira ferment has shown a great number of wild yeasts and a lower number of total yeasts, however, there was no difference in the number of bacteria comparing to the fermentation with a commercial strain. For the latter, an increased or stabilized number of wild yeasts was observed along the fermentative cycles, white for the caipira ferment this number decreased or stabilized. There was an intense acidification of the medium during the preparation of the caipira ferment, which was repeated in the initial cycles of the fermentation with this ferment, decreasing afterwards. Significant alterations in the composition of redistilled cachaças were observed after ageing in oak barrels, especially concerning to pH, total acidity (fixed and volatile), alcoholic content and secondary compounds, as npropanol, acetaldehyde, isobutanol and total volatile compounds. All the parameters presented values within the limits of Brazilian laws. The type of the ferment influenced the beverage quality, because the cachaça produced with the caipira ferment has shown increased fixed acidity with the ageing, while for the one produced with the commercial strain, there was an increase in the volatile acidity. The sensory tests of preference revealed that the cachaças produced with the caipira ferment were significantly different (p<0.05) from the cachaças produced with the commercial strain regarding the aroma and global impression, after ageing. Although the fermentation with caipira ferment has shown a great number of wild yeasts in the inoculum and in the sugar cane juice, the cachaça produced with this ferment showed better preference. There were no differences in the sensory tests concerning both ferments for the non-aged cachaças, showing that not only the ageing influenced the quality of the cachaça, but also the type of ferment utilized in the fermentation for the cachaça production.